1998
DOI: 10.1111/j.1440-1843.1998.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of sialylated carbohydrate antigens, KL‐6, CA19‐9 and SLX as serum markers for interstitial pneumonia

Abstract: We compared diagnostic values of three serum carbohydrate antigens, KL-6, CA19-9 and SLX to discriminate interstitial pneumonia (IP) from alveolar pneumonia and healthy volunteers. Subjects consisted of 13 patients with idiopathic pulmonary fibrosis and 10 associated with collagen vascular diseases, 12 patients with sarcoidosis and 70 controls (52 healthy volunteers and 18 patients with alveolar pneumonia). Cut-off values were determined at the level at which the diagnostic accuracy became the highest for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…However, CA 19-9 may be increased in other malignancies such as ovarian cancer, colon cancer, and gastric cancer (16). In addition, CA 19-9 increases have been reported in various benign conditions such as Hashimoto's thyroiditis (16), benign biliopancreatic diseases (17), and several lung diseases (6)(7)(8)(9). In the present study, 11 (8.5%) out of 130 participants with increased CA 19-9 had malignancy; only five of which had pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, CA 19-9 may be increased in other malignancies such as ovarian cancer, colon cancer, and gastric cancer (16). In addition, CA 19-9 increases have been reported in various benign conditions such as Hashimoto's thyroiditis (16), benign biliopancreatic diseases (17), and several lung diseases (6)(7)(8)(9). In the present study, 11 (8.5%) out of 130 participants with increased CA 19-9 had malignancy; only five of which had pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In consistency with previous reports in the literature {Takayama et al [70]}, authors demonstrated a strong correlation of serum levels with the degree of disease activity indicating a potential role of these molecules as prognostic markers of disease severity and therapeutic response. Furthermore, Yokoyama et al [71] carried out the first comparative evaluation of the diagnostic values of three serum carbohydrate antigens (KL-6, Ca 19-9, and SLX). They plotted ROC curves and demonstrated a clear superiority in terms of specificity, sensitivity and diagnostic accuracy of KL-6 plasma levels in discriminating interstitial pneumonia from alveolar pneumonia and healthy volunteers.…”
Section: Serum Biomarkers In Idiopathic Pulmonary Fibrosis and Colmentioning
confidence: 99%
“…16 20 21 31 Obayashi et al 31 showed that BAL fluid concentrations of CA19-9 correlated with other markers of inflammation including elastase, hepatocyte growth factor, and lactic acid dehydrogenase in patients with IPF, and that CA19-9 had a chemotactic activity for neutrophils. In this study, however, there were no significant differences in the serum levels of SLX and CA19-9 between all the groups.…”
Section: Discussionmentioning
confidence: 99%